Scandalous love - Joyce, Brenda New York Times Bestselling Author (New York, U.S.A. : Avon Books, 1992)
Obsessed by Nicole's daring conduct and sensuality but bound by the dictates of duty and honor to another woman, Hadrian resolves to have the raven haired beauty as his mistress... though never as his bride. But Nicole will be no man´s plaything. She will risk pain and heartbreak to satisfy her wild, uncompromising passion - determined to win the handsome Duke´s unwavering devotion... and his undying love.
Capítulo 1 al 36
Keywords: NORTH AMERICAN LITERATURE; ENGLISH LITERATURE